DERIVATIVE SECURITIES IN THE FINANCIAL RISK HEDGING SYSTEM - Bashlai, Serhii (Sworld-Us Conference proceedings, 2025)
The article is devoted to the study of the efficiency of using derivatives as financial risk hedging instruments in the context of exchange activities. The article pays special attention to the analysis of the effectiveness of the use of exchange derivati